2016
DOI: 10.1016/j.jfluidstructs.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Time domain simulation of vortex-induced vibrations in stationary and oscillating flows

Abstract: This paper focuses on the further development of a previously published semi-empirical method for time domain simulation of vortex-induced vibrations (VIV). A new hydrodynamic damping formulation is given, and the necessary coefficients are found from experimental data. It is shown that the new model predicts the observed hydrodynamic damping in still water and for cross-flow oscillations in stationary incoming flow with high accuracy. Next, the excitation force model is optimized by simulating the VIV respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…This may induce transient effects and stability problems in the time integration process. This is why Thorsen et al (2016) proposed a smoothed amplitude response curve, which converges towards the solution obtained by equation 25, when the vibrations reach steady-state. The same smoothing technique is utilized in the proposed in-line VIV model.…”
Section: Determination Of Amplitude and The Instantaneous Phase Of Cymentioning
confidence: 83%
See 1 more Smart Citation
“…This may induce transient effects and stability problems in the time integration process. This is why Thorsen et al (2016) proposed a smoothed amplitude response curve, which converges towards the solution obtained by equation 25, when the vibrations reach steady-state. The same smoothing technique is utilized in the proposed in-line VIV model.…”
Section: Determination Of Amplitude and The Instantaneous Phase Of Cymentioning
confidence: 83%
“…In Thorsen et al (2014a), the model is seen to produce realistic results for both forced and free oscillation tests of rigid cylinders, and free oscillations of flexible cylinders. Through several case studies, a high degree of realism is found for numerical simulations of flexible pipes with circular cross section in uniform and sheared current (Thorsen et al, 2014b(Thorsen et al, , 2015a, and in oscillating flow (Thorsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, numerical models could lead to a full characterization of hydrodynamics coefficients in a wide range of Reynolds number and Keulegan-Carpenter number. Fu et al (2014) and Thorsen et al (2016) present interesting results of hydrodynamic forces on a flexible cylinder. Further experiments in order to assess the inertia coefficient would assist towards a deeper understanding of added mass results obtained in the present work.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, the recent work by Thorsen et al (2016), e.g., on flexible cylinders in oscillating flows, still uses C a = 1 in its proposed empirical hydrodynamic model. The experimental work by Fu et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation